2016
DOI: 10.1007/s13205-016-0376-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation, carotenoid, fatty acid and tocopherol content of Ajuga multiflora Bunge

Abstract: The effect of plant growth regulators on shoot proliferation from shoot tip explants of Ajuga multiflora was studied. The highest number of shoots (17.1) was observed when shoot tip explants were cultured on Murashige and Skoog (MS) medium fortified with 8.0 µM 6-Benzyladenine (BA) and 2.7 µM α-naphthaleneacetic acid (NAA). The mean number of shoots per explant was increased 1.6-fold in liquid medium as compared with semi-solid medium. Maximum rooting (100 %) with an average of 7.2 roots per shoot was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
6
12
0
Order By: Relevance
“…Helium was used as the carrier gas. Firstly, column temperature was maintained at 120°C for 5 min, followed by increasing the temperature to 240°C in 30 min using a linear temperature program of 4°C/min and held at 240°C for 25 min (Sivanesan et al, 2016a ). The FAMEs were identified by comparing their fragmentation pattern and retention time with authentic standards and also with the database from the National Institute Standard and Technique (NIST)/Environmental Protection Agency (EPA)/National Institutes of Health (NIH) Mass Spectral Database (NIST08 and NIST08S) Library (Saini et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Helium was used as the carrier gas. Firstly, column temperature was maintained at 120°C for 5 min, followed by increasing the temperature to 240°C in 30 min using a linear temperature program of 4°C/min and held at 240°C for 25 min (Sivanesan et al, 2016a ). The FAMEs were identified by comparing their fragmentation pattern and retention time with authentic standards and also with the database from the National Institute Standard and Technique (NIST)/Environmental Protection Agency (EPA)/National Institutes of Health (NIH) Mass Spectral Database (NIST08 and NIST08S) Library (Saini et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…The establishment of in vitro cell and organ cultures of S. dasyphyllum will be useful for secondary metabolite production. Several bioactive compounds like alkaloids, carotenoids, fatty acids, flavonoids, phenolic acids and tocopherols were obtained from in vitro shoot cultures of important plants (Jeong and Sivanesan, 2015 , 2016 ; Sivanesan et al, 2016a , b ; Dowom et al, 2017 ; Grzegorczyk-Karolak et al, 2017 ). Till date, no published reports are available on the micropropagation of S. dasyphyllum .…”
Section: Introductionmentioning
confidence: 99%
“…The content of secondary compounds in cell and organ cultures was signicantly enhanced by optimizing the composition of the culture medium, incorporation of precursors and elicitors and providing appropriate culture conditions. 83,[88][89][90] NPs added to the plant in vitro culture medium may act as a nutrient source and an elicitor. Poborilova et al 67 reported that the addition of Al 2 O 3 NPs (10-100 mg mL À1 ) to tobacco cell suspension cultures signicantly increased the phenolic content.…”
Section: Nanomaterials Enhancement Of Secondary Metabolitesmentioning
confidence: 99%
“…Lipid extraction was performed (in triplicate) using chloroform-methanol extraction, based on methodology reported by Bligh and Dyer (1959), and Sivanesan et al (2016) with minor modifications. Briefly, one whole tomato fruit was finely chopped and homogenized in a food processor, and five grams of homogenized fruit (exact to 0.001 g) from each ripening stage were separately transferred into a test tube containing 20 ml mixture of chloroform and methanol (2:1 v/v).…”
Section: Lipid Extraction and Fatty Acid Methyl Esters (Fames) Preparmentioning
confidence: 99%